1977
DOI: 10.1046/j.1537-2995.1977.17177128894.x
|View full text |Cite
|
Sign up to set email alerts
|

Viability and Function of Platelets Frozen at 2 to 3C per Minute with 4 or 5 Per Cent DMSO and Stored at −80C for 8 Months

Abstract: Each of 15 healthy male volunteers was treated with 650 mg of aspirin 24 hours before the autologous transfusion of one unit of freeze-preserved platelets. Freeze-thaw-wash recovery values in vitro, viability and function in vivo, and the bleeding time and platelet aggregation response were measured. The platelets were frozen with 4 or 5 per cent dimethylsulfoxide (DMSO) at an overall rate of 2 to 3 C per minute and were stored at -80 C in a mechanical freezer for up to eight months. They were washed by diluti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
25
0

Year Published

1979
1979
2018
2018

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 17 publications
2
25
0
Order By: Relevance
“…In addition to the enhanced recovery of circulating platelets, an important consequence of the use of Thrombo-Sol is the ability to reduce the requirement for DMSO as a cryoprotectant. Previous studies testing the use of reduced concentrations of DMSO during infusion indicated that the recipients showed no adverse effects, even following a 10year period (Handin & Valeri, 1972;Lazarus et al, 1981;Melaragno et al, 1985;Spector et al, 1977). The development of a cryopreservation system that contains transfusable components would eliminate both the damaging effects of the wash step and the need to break the closed system.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the enhanced recovery of circulating platelets, an important consequence of the use of Thrombo-Sol is the ability to reduce the requirement for DMSO as a cryoprotectant. Previous studies testing the use of reduced concentrations of DMSO during infusion indicated that the recipients showed no adverse effects, even following a 10year period (Handin & Valeri, 1972;Lazarus et al, 1981;Melaragno et al, 1985;Spector et al, 1977). The development of a cryopreservation system that contains transfusable components would eliminate both the damaging effects of the wash step and the need to break the closed system.…”
Section: Discussionmentioning
confidence: 99%
“…Our laboratory has utilized the aspirin‐induced thrombocytopathy to increase the BT and reduce the thromboxane level in the shed blood to assess PLT function of fresh and preserved PLTs in normal volunteers and in baboons 162‐168 . In addition, our laboratory has studied the survival and function of fresh and preserved PLTs in anemic thrombocytopenic patients with prolonged BTs with and without nonsurgical blood loss 169,170 …”
Section: Effects Of Temperature Hct Plt Count and Plt Function On mentioning
confidence: 99%
“…12 Cryoplatelets have been transfused in healthy volunteers, generally yielding lower count increments compared to liquid-stored PLTs. 5,13,14 This is caused by biochemical changes during cryopreservation that can be detected in vitro including decreased PLT aggregation, deficient signal transduction, altered morphology, differential expression of certain membrane markers, and microparticle release. [14][15][16][17][18] Recent studies suggest that cryoplatelets are procoagulant, 19,20 but these experiments were performed in static conditions when hemostasis was not restricted by convective hydrodynamic forces.…”
mentioning
confidence: 99%